Crushing behaviour of kenaf fibre-reinforced epoxy composite elliptical tubes - M Alkateb, Mohamed Mohamed (2018)
Design selection is an important topic in the industry to manufacturing sustainable and competitive products. To meet the needs of strength and durability at component level, the shape can be used as a design tool during the early stages of the design process.The familiar range of tubular sections such as namely square, rectangular and circular hollow sections, this study attempts to addition a new hollow sections is elliptical tubes to tubular family. The new sections combine the elegance of circular hollow sections with the improved structural efficiency under crushing load conditions due to the differing flexural rigidities about the two principal axes. The purpose of this research is to study and analyzed crushing behaviour of composite elliptical tubes on the energy absorption. The main materials used in this project are unsaturated polymer resin, kenaf and wool fibers. A hand lay-up technique was used to fabricate the specimens of composite elliptical tubes. The specimens are tested for the quasi-static compressive testing. Four objectives were performed for crushing test. The first objective was to study the effect of vertex angles on crashworthiness parameters, energy absorption and failure mode; the vertex angles vary from 0° to 24° in 6° increments, the specific energy absorption for the composite elliptical cones showed a positive correlation, i.e., the vertex angle increased, the more energy was absorbed. In this regard, composite elliptical cone with the vertex angle is 24º exhibited the highest specific energy absorption capability equal to 441.473 kJ/kg. The objective two was devoted to study the effect of holes on crushing behaviour of composite elliptical tubes under axial load, four different elliptical tubes; three tubes with holes of (4, 6 and 8) and one without holes at same dimensions. Crushing behavior of kenaf composite elliptical tubes was affected by holes in their wall, results kenaf tubes without holes attributed to a lower initial peak load, (Pi) followed by a lower mean crush load compared with other tubes. It was clear from resulte that the average crush load increaes when holes increaes. Furthermore, On the other hand, it can be noticed that the kenaf tube with holes of 8 resulted the best specific energy (Es) of (486.207kJ/kg ) as well as biggest value of average crushing load equal to 21.043kN. Objective three involved fabrication and testing of four elliptical tubes, three supported by wooden sticks (four, six, and eight sticks) and unsupported to determine the effect of supported on crashworthiness parameters of natural kenaf fibre reinforced composite elliptical tubes. The supported can control the load distribution during the crushing period and can increase the carrying loads of the structure. The results revealed that all specimens have failed in longitudinal failure modes; the number of wooden sticks increases the more energy absorbed. . In this regard, the tube with eight wooden sticks exhibited the highest specific energy absorption capability of 570.7329 kJ/kg and highest value of the average load of 12.401 kN. The last objective, was to study the effect of fibre content on the crashworthiness parameters, energy absorption and the failure modes of kenaf fibre- reinforced elliptical composite.tube. Various fibre contents were considered, including 30%, 35% and 40%. Reinforced fibers are strong and effective for improving the mechanical properties of composite materials. One the other hand, wool fibre used for reinforced elliptical composite tube to investigate the effect of fiber type on crashworthiness parameters and energy absorption. The main goal is to maximize the amount of impact energy absorbed, improve crashworthiness parameters in tube structure and at the same time minimize its weight. The methodology is based on comparison between kenaf and wool tube type with fiber content of 30%, 35% and 40%. It should be noted that an increase in the fiber content might not always necessarily improve the specific energy absorption capability. As the fiber volume fraction increases, the volume of the matrix between the fibers decreases. In this regard, the fiber content increases the specific energy absorption capability decreases. Overall, the wool tube with fiber content of 30% have the best value of specific energy absorption of 235.646kJ/kg. Above all, the experimental tests considered in this study results that the tube supporting by wooden sticks of 8 exhibited the highest specific energy absorption capability compared to all other tested samples. Furthermore, it was observed that tubes with wooden sticks of 8 displayed the specific energy absorption 570.7329 kJ/kg greater than those tubes with holes, vertex angle, fibre content respectively. The specific energy absorption by wool tube greater than that kenaf tube in the rate of 16%.